IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL DALAM MEWUJUDKAN KUALITAS SUMBER DAYA MANUSIA PENDIDIKAN - Ida Farida; Muhammad Zuhaery; Dian Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine how school principals implement transformational leadership in an effort to improve the quality of human resources (HR) in education at SDIT Jayapura. The approach used is a qualitative approach with a case study design. Data collection techniques were carried out through observation, in-depth interviews, and document study. The informants in this study include the principal, permanent teachers, and student representatives. The research findings indicate that the school principal implements four dimensions of transformational leadership. First, idealized influence is demonstrated through exemplary behavior in discipline, integrity, spirituality, and an inclusive attitude. Second, inspirational motivation is reflected through verbal and nonverbal support for teachers, viewing the profession as a form of worship, and a culture of sharing best practices within the school environment. Third, intellectual stimulation is shown through the encouragement of critical, creative, and continuous thinking, although the description only mentions this through examples of discipline and integrity. Fourth, individual consideration is evident in the principal's attention to the individual needs of both teachers and students, although this is not explicitly stated.The implementation of transformational leadership has a positive impact on improving the quality of educational human resources, such as increased teacher commitment, enjoyable and innovative learning, a positive work culture, adequate facilities, and harmonious interpersonal relationships. Students also experience a comfortable learning environment and enjoyable interaction with their teachers. In conclusion, transformational leadership is a crucial key in building excellent educational human resources and improving the quality of education in integrated Islamic schools.